Radiological outcomes of surgical techniques for spastic hip in cerebral palsy: a systematic review and meta-analysis - Iman Menbari Oskouie; Alireza Hakiminejad; Amirali Yazdanmehr; Keihan Mostafavi; Asma Mafhoumi; Amir H. Sajedi; Ali Roosta; Alireza Arvin; Ana Presedo; Mohammad Hossein Nabian; Amir Kasaeian (Journal of Orthopaedics and Traumatology, 2025)
Abstract Background In patients with cerebral palsy (CP), spastic hip is a prevalent complication. Various surgical approaches,, including pelvic osteotomy (PO), femoral osteotomy (FO), combined femoral and pelvic osteotomy (CFPO), and soft tissue surgery (STS), have been used to address this problem. This systematic review and meta-analysis was designed to compare the radiologic outcomes of these interventions for spastic hip in patients with CP. Methods To identify relevant studies, databases were searched using specific keywords. Initially, duplicates were removed, then the titles and abstracts were screened, followed by a comprehensive full-text review. Data extraction took place from the studies that met the inclusion criteria. Subsequently, a meta-analysis was conducted. Results The analysis of 6116 hips from 4546 patients across 81 studies demonstrated that PO significantly enhanced the center–edge angle (CEA), reduced the acetabular index (AI) and migration percentage (MP), and improved the Sharp and Tönnis angles. FO led to a substantial decrease in AI and MP, though CEA did not show a significant change, while CFPO resulted in significant improvements across AI, MP, neck-shaft angle (NSA), CEA, Sharp angle, and Tönnis angle. STS did not show significant changes in AI or CEA, but MP was notably reduced. Tone-decreasing procedures, such as selective dorsal rhizotomy and botulinum toxin injections, did not significantly alter MP, whereas guided growth techniques showed a significant reduction. MP improvements in FO decreased over time, with other radiologic parameters remaining relatively stable as follow-up increased. Age-specific trends indicated that children under 6 years primarily underwent tone-decreasing procedures and STS, while those around 7 years favored FO and guided growth, and older children (over 9 years) more commonly underwent PO, CFPO, or percutaneous osteotomy. Comparative analysis showed PO and percutaneous osteotomy were particularly more effective in reducing MP, with PO also being superior for AI improvement; whereas CFPO provided better outcomes for enhancing CEA. No significant differences were found among surgical methods for improving NSA. Conclusions This systematic review and meta-analysis underscores the superior efficacy of PO and CFPO in correcting spastic hip deformity in children with CP. Radiological outcomes demonstrate significant improvements following these procedures. The findings suggest that these approaches are particularly effective for complex cases where procedures such as FO, STS, or TDS may fall short. Future studies should focus on refining surgical protocols and exploring the long-term functional outcomes of these interventions.